1997
DOI: 10.1001/archinte.1997.00440410077008
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Mammography Use in the Inner City

Abstract: Personalized education and case management are successful in enhancing compliance with breast cancer screening among historically noncompliant vulnerable urban women. This intervention, when combined with a preventive care information system, has the potential to achieve Healthy People 2000 objectives for breast cancer screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(9 citation statements)
references
References 29 publications
0
8
1
Order By: Relevance
“…However, given these differences, the results of the stepwise multicomponent intervention were consistent with at least two other studies testing multistrategy approaches in low income women, albeit with lower rate increases. Compared with the 27% increase seen in our stepwise intervention group, Weber et al (37) found a 41% increase and Champion et al (38) found a 49% to 55% increase through the use of multicomponent interventions. Other studies have shown mixed results (39) or nonsignificant results (40).…”
Section: Discussioncontrasting
confidence: 68%
“…However, given these differences, the results of the stepwise multicomponent intervention were consistent with at least two other studies testing multistrategy approaches in low income women, albeit with lower rate increases. Compared with the 27% increase seen in our stepwise intervention group, Weber et al (37) found a 41% increase and Champion et al (38) found a 49% to 55% increase through the use of multicomponent interventions. Other studies have shown mixed results (39) or nonsignificant results (40).…”
Section: Discussioncontrasting
confidence: 68%
“…Native-American and Southeast-Asian women, who had the lowest screening rates, had 20% to 25% improvements. Similar interventions, some of which included referral to a nurse practitioner, have been successful in primary care and emergency department settings, 14,15,[17][18][19] but have not been tested previously in non-primary-care clinics. Approximately one quarter of our study participants could not identify a regular health care provider.…”
Section: Discussionmentioning
confidence: 99%
“…This approach has been successful in primary care settings, [14][15][16][17] and in a public hospital emergency department. 18 Some studies have used nurses to deliver screening recommendations; however, several studies involving minority populations have employed culturally sensitive lay health advisers in medical settings 19 and in the community. 14,20,21 These studies have demonstrated the ability of trained lay workers to counsel women who have not responded to or have not received screening recommendations from traditional health care providers.…”
mentioning
confidence: 99%
“…For example, a nurse-initiated prompting system, flow sheets, and computerized reminders have all been shown to increase the delivery of preventive services [33][34][35][36] and may be well advised here. Among urban minorities, compliance with preventive measures has been enhanced by an intense, personal intervention designed to remove barriers to care, 37 and by computerized patient reminders. 38 Other interventions such as mobile units, videotapes, culturally relevant educational material, 39 or site of service modification 34 also may be useful in caring for AI/AN populations.…”
Section: Discussionmentioning
confidence: 99%